Application of Emotional Branding Strategy in the Model Development of Sports Brand of The Bottled Water Market - Marija Jankovic (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2017)
The new economy has brought new meaning to the brand, which is characterized by a brand, but also has a human touch, turning into an emotional brand. Alternative branding strategies put emphasis on brand experience in terms of emotional, holistic and socially responsible. Bottled water has become the world's "liquid gold" in the last 40 years, because it is a natural product, which is made with minimal costs. The paper develops the idea to perform a kind of humanization and the introduction of a new emotional brand of bottled water on the market, which will bear the name "Aqua F.I.F.A" designed label of FIFA international organizations, as well as the roof of the organizers of the most important football events in the world and the label of the national team. This paper will analyze in detail the market opportunities and prospects of introducing a unique sports brand, on the emotional aspect, with the use of effective marketing communication strategy.